Organic carbon and lignin in the upper layer of bottom sediments in Kandalaksha Gulf, White Sea. - Peresypkin, Valery I; Shcherbakov, Fyodor A (PANGAEA, 1992)
Data on distribution of organic carbon and phenols near the top of Kandalaksha Gulf, one of the largest gulfs of the White Sea, are presented. Investigations carried out the port city of Kandalasksha indicate that bottom sediments of the area adjoining the port contain synthetic phenols and have elevated concentrations of organic carbon. But in general sediments of this part of the gulf have near-normal concentration and composition of both phenols and organic carbon. This indicates that ecological situation in this area remains near-optimal.
Concentration of phenols in bottom sediments from the Kandalaksha Bay, White Sea
Keywords: Acetosyringone; Acetovanillone; Archive of Ocean Data; ARCOD; Carbon, organic, total; Carbon analyser AN-7529, 7560; Chromatographic; DEPTH, sediment/rock; Grab; GRAB; Kandalaksha Bay, White Sea; KB-PS92-44; KB-PS92-47; KB-PS92-48; KB-PS92-49; KB-PS92-52; KB-PS92-56; KB-PS92-57; KB-PS92-58; KB-PS92-59; KB-PS92-62; KB-PS92-63; KB-PS92-64; KB-PS92-65; KB-PS92-99; Phenols; p-Oxyacetophenone; p-Oxybenzaldehyde; p-Oxybenzoic acid; Ratio; Syringcaldehyde; Syringic acid; Vanillic acid; Vanillin